2022
DOI: 10.1002/1878-0261.13304
|View full text |Cite
|
Sign up to set email alerts
|

Identification and targeting of a HES1‐YAP1‐CDKN1C functional interaction in fusion‐negative rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS), a cancer characterized by features of skeletal muscle, is the most common soft‐tissue sarcoma of childhood. With 5‐year survival rates among high‐risk groups at < 30%, new therapeutics are desperately needed. Previously, using a myoblast‐based model of fusion‐negative RMS (FN‐RMS), we found that expression of the Hippo pathway effector transcriptional coactivator YAP1 (YAP1) permitted senescence bypass and subsequent transformation to malignant cells, mimicking FN‐RMS. We also found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Since, all three NOTCH receptors are shown to have important roles in rhabdomyosarcoma differentiation, our study is not designed to dissect the roles of individual receptors. 9 , 33 , 34 , 36 , 37 However, we can infer the following based on our analyses. We have previously shown that knockdown of NOTCH1 results in increased MYOG, MEF2C resulting in robust differentiation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since, all three NOTCH receptors are shown to have important roles in rhabdomyosarcoma differentiation, our study is not designed to dissect the roles of individual receptors. 9 , 33 , 34 , 36 , 37 However, we can infer the following based on our analyses. We have previously shown that knockdown of NOTCH1 results in increased MYOG, MEF2C resulting in robust differentiation.…”
Section: Discussionmentioning
confidence: 93%
“… 39 In addition, NOTCH1 and or 3 may also partially suppress differentiation via regulating NOTCH targets genes HES1 and HEY1 involved in differentiation through EBox independent mechanisms. 33 , 36 Second, SNAI2 may have NOTCH independent effects on regulating self-renewal, as sphere formation is still disrupted in SNAI2 knockout RD cells. Finally, since the effects we have outlined may occur in different cell subpopulations i.e.…”
Section: Discussionmentioning
confidence: 99%